Kinematic and kinetic characteristics of vertical jump: comparison between soccer and basketball players - Matheus Machado Gomes; Gleber Pereira; Paulo Barbosa de Freitas; José Angelo Barela (Universidade Federal de Santa Catarina, 2009)
The aim of this study was to compare jump height and kinetic and kinematic com-ponents of countermovement vertical jumps between soccer and basketball players performed in two different arm swing conditions: with arm swing (WAS) and without arm swing (NAS). Nine basketball players (21.2 ± 2.9 years; 101.64 ± 14.58 kg; 1.95 ± 0.06 m) and nine soccer players (18.2 ± 0.7 years; 77.4 ± 7.58 kg; 1.81 ± 0.07 m) performed 12 maximal countermo-vement vertical jumps, including 6 WAS jumps and 6 NAS jumps, on a force platform that recorded the ground reaction force (GRF). The vertical component of the GRF was used to estimate jump height and to calculate the kinematic (duration of eccentric phase, duration of concentric phase, and maximal downward displacement of center of mass) and kinetic variables (mean power during the eccentric phase, mean power during the concentric, peak power, and peak force). The results showed no differences in jump height or in kinematic or kinetic variables between basketball and soccer players. In addition, the results showed that the participants of the two groups jumped higher in the WAS condition (0.41 m) than in the NAS condition (0.36 m) because of a higher peak power (WAS=276.8 W/kg0.67 and NAS=241.3 W/kg0.67) and a longer concentric phase duration (WAS=0.20 s/m0.5 and NAS=0.19 s/m0.5) during WAS jump. These results indicate that the basketball and soccer players studied here showed similar performance and the same kinematic and kinetic pattern in maximal vertical jumps and were comparably affected by the use of arm swing.